2016
DOI: 10.1371/journal.pone.0161859
|View full text |Cite
|
Sign up to set email alerts
|

The Silencing of CCND2 by Promoter Aberrant Methylation in Renal Cell Cancer and Analysis of the Correlation between CCND2 Methylation Status and Clinical Features

Abstract: Cyclin D2 (CCND2) is a member of the D-type cyclins, which plays a pivotal role in cell cycle regulation, differentiation and malignant transformation. However, its expression status and relative regulation mechanism remains unclear in renal cell cancer (RCC). In our study, the mRNA expression level of CCND2 is down-regulated in 22/23 paired RCC tissues (p<0.05). In addition, its protein expression level is also decreased in 43/43 RCC tumor tissues compared with its corresponding non-malignant tissues (p<0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Among the genes upregulated in eggs from wild fish, ccnd2 and hras were found to be also involved in cell cycle progression. Importantly, modified expression of these genes led to gonadal ( ccnd2 ; Sicinski et al, 1996; Wang et al, 2016) and cervical ( hras ; Córdova‐Alarcón, Centeno, Reyes‐Esparza, García‐Carrancá, & Garrido, 2005) cancer. On the contrary, the genes upregulated in eggs of domesticated fish were involved in the reception of ubiquitination signals and in the activation of the IKK complex ( ikbkg ; Israël, 2010; Muller, Baeyens, & Dustin, 2018); these were also involved in the negative regulation of the Ras–ERK pathway ( spred1 ; Suzuki, Morita, Hirata, Shichita, & Yoshimura, 2015), confirming that intracellular signaling (involving PTMs) should be considered as crucial in the process of fish domestication.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes upregulated in eggs from wild fish, ccnd2 and hras were found to be also involved in cell cycle progression. Importantly, modified expression of these genes led to gonadal ( ccnd2 ; Sicinski et al, 1996; Wang et al, 2016) and cervical ( hras ; Córdova‐Alarcón, Centeno, Reyes‐Esparza, García‐Carrancá, & Garrido, 2005) cancer. On the contrary, the genes upregulated in eggs of domesticated fish were involved in the reception of ubiquitination signals and in the activation of the IKK complex ( ikbkg ; Israël, 2010; Muller, Baeyens, & Dustin, 2018); these were also involved in the negative regulation of the Ras–ERK pathway ( spred1 ; Suzuki, Morita, Hirata, Shichita, & Yoshimura, 2015), confirming that intracellular signaling (involving PTMs) should be considered as crucial in the process of fish domestication.…”
Section: Discussionmentioning
confidence: 99%
“…After PDR3 treatment, we identified DMRs at the promoters of CCND2, ZNF286A, ZNF607, and ZNF876P. CCND2 plays a pivotal role in cell-cycle regulation, differentiation, and malignant transformation, 56 and loss of CCND2 is closely associated with aberrant promoter methylation 57 . Our results suggest that hypomethylation of CCND2 might promote the transcriptional activation of tumor suppressors.…”
Section: Discussionmentioning
confidence: 69%
“…Reduced expression of cyclin D2 was observed in breast cancer, non‐small cell lung cancer, pancreatic cancer and prostate cancer, indicating that cyclin D2 may act as a tumour suppressor in these cancers 36‐39 . Loss of CCD2 gene, which encodes cyclin D2, was also observed in renal cell cancer tissues and is correlated with aberrant methylation 40 . Moreover, Meyyappan and colleagues reported that overexpression of cyclin D2 in human fibroblast cells leads to inhibition of cell cycle progression and DNA synthesis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] Loss of CCD2 gene, which encodes cyclin D2, was also observed in renal cell cancer tissues and is correlated with aberrant methylation. 40 Moreover, Meyyappan and colleagues reported that overexpression of cyclin D2 in human fibroblast cells leads to inhibition of cell cycle progression and DNA synthesis. 41 42,43 Furthermore, overexpression of MMP-2 and MMP-9 was observed in ovarian cancer, 44 and knockdown of both MMP proteins diminished the cell invasiveness of ovarian cancer.…”
Section: Control Shugdhmentioning
confidence: 99%